PENGEMBANGAN DISTRIBUSI PEMASARAN IKAN KERING DI KECAMATAN SASAK - Muchia Desda, Mia; Yuliza, Mai (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
This study aims to socialize simple bookkeeping for SMEs salted fish fisheries in Kampung Padang Nagari Air Bangis. The method used in implementing this Student Creativity Program (PKM) activity is through two methods, namely socializing the role of simple bookkeeping for the development of SMEs and providing an example in calculating production costs in a dried fish business as well as examples of calculating production costs incurred during one production process. Based on the results of interviews conducted with the jorong head of Padang Air Bangis Village, there are 320 families where 90% of the main livelihoods of their residents are engaged in fisheries which are divided into several businesses, namely as bagan fish (fishing gear) owners, fishermen, fish traders, fish dryer and owners of salted fish business. Meanwhile, 10% are engaged on odd jobs, namely as rope rollers. Limited capital for business development becomes an obstacle when they are required to seek alternative financing from capital institutions or banks that impose administrative requirements. It demonstrates an increase in knowledge and understanding of the benefits of simple bookkeeping and other types of financial reports as a result of service activities in the form of socialization.